Pregnancy identity card of women with fetal death in utero: case-control study in a reference hospital in metropolitan Cameroon - Metogo Ntsama, Junie Annick; Tatsipie, Wilfried Loic; Bayokolak, Amandine; Mboua, Veronique Batoum; Mbianda, Chanelle; Um, Esther Meka Ngo; Ndoua, Claude Cyrille Noa; Foumane, Pascal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Intrauterine fetal death is the death of the fetus in the uterus beyond 22 weeks of gestational age and/or weighing 500g. It is frequent in developing countries, showing that, efforts and progress still need to be made in the follow-up of high risk pregnancies. The general objective of our study was to identify the associated factors of intrauterine fetal death at the Yaounde gynaeco-obstetric and paediatric hospital. Methods: We conducted a case-control study at the Yaounde gynaeco-obstetric and pediatric hospital from January 1 April to 30April 2021. The cases were all women admitted in the service of obstetrics and gynaecology with fetal death from 22 completed weeks of gestation and above confirmed by ultrasound and willing to participate in the study and the controls were any women admitted in the service who gave birth to a live fetus and willing to participate with maternal age as the matching criteria. We recruited 42 cases for 84 controls making one case for two controls. The statistical analysis was done using SPSS software version 23.0 and excel 2016. Results: The associated factors for intrauterine fetal death found during our study were: being single (ORa=3,6; CI= 1.3-1.9), less than four antenatal consultations (ORa=3.6; CI=1.3-10.1) and being followed by a midwife (ORa=6.6; CI=1.0-41.7). Conclusions: The elements of the identity card of a pregnant woman with fetal death in utero are: being single, less than four antenatal consultations and being followed by a midwife.